(untitled) (Proceedings of the Society of Antiquaries of Scotland, 1859)
The author quotes extensively from 15th- to 17th-century record books found in the burgh of Haddington to demonstrate the variety of their contents. The books discuss specific events such as legal proceedings and buildings contracts, how the town dealt with incidents of criminality of public health and safety, the election of officials such as bailies and clerks, as well as the names of some of these officers and the town’s provosts. The article concludes by focusing on two cases: the first relating to the marriage of Nicol Ramsay and Christiane Ross and the second relating to issues amongst the monks of Newbattle Abbey.